2020
DOI: 10.1029/2019jc015420
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale Topographic Form Stress and Local Dynamics of the Southern Ocean

Abstract: The contribution of small‐scale abyssal hill topography to the topographic form stress and local dynamics of the Southern Ocean is investigated using a high‐resolution model of the sector of the Southern Ocean south of Tasmania and New Zealand. The results of two simulations, with and without small, O(1–100 km), scale topography, confirm that the effects of small‐scale topography are exerted through the generation of strong topographic form stress leading to transient eddy dissipation and changes in flow meand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…The EKE over the shelf is generally suppressed in the SRTM15 simulation. The response of the ocean circulation to seafloor roughness over the continental shelf is consistent with the results and mechanisms described in previous studies of the Southern Ocean 50,71 , showing that seafloor roughness applies a drag to the deepreaching currents and eddies leading to a decrease in their kinetic energy. In the SRTM15 simulation, the AACC experiences a stronger drag from seafloor roughness over the shelf, and becomes weaker and less efficient at transporting water westward across the region.…”
Section: Regional Circulationsupporting
confidence: 90%
See 2 more Smart Citations
“…The EKE over the shelf is generally suppressed in the SRTM15 simulation. The response of the ocean circulation to seafloor roughness over the continental shelf is consistent with the results and mechanisms described in previous studies of the Southern Ocean 50,71 , showing that seafloor roughness applies a drag to the deepreaching currents and eddies leading to a decrease in their kinetic energy. In the SRTM15 simulation, the AACC experiences a stronger drag from seafloor roughness over the shelf, and becomes weaker and less efficient at transporting water westward across the region.…”
Section: Regional Circulationsupporting
confidence: 90%
“…As a result, the presence of CDW over the shelf is reduced. Previous studies for the Southern Ocean show that it is the topographic form stress arising from seafloor roughness that impacts the large-scale motions such as currents and eddies 50,71 . Some of the topographic form stress is associated with the lee wave generation 75 , while some can be associated with Rossby waves and other non-radiating motions generated by topographic features 76 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also found the inclusion of rough topography can modify the mean flow path (e.g., de Marez et al, 2020;Zhang & Nikurashin, 2020). This influence of the rough topography on mean flow may further affect the eddy energy, since the eddies are mainly generated through instabilities of the mean flow.…”
Section: Reduced Eddy Scales In the Ocean Interiormentioning
confidence: 96%
“…It has been shown that the eddy saturation regime is approached when the horizontal resolution of ocean models is high enough to resolve the eddy energy generation processes (i.e., the Rossby radius of deformation; Farneti et al., 2010; Hallberg & Gnanadesikan, 2001, 2006; Morrison & Hogg, 2013; Munday et al., 2013; Tansley & Marshall, 2001). However, the eddy energy dissipation processes have also been shown to impact the eddy characteristics in the Southern Ocean (e.g., Trossman et al., 2013, 2016; Zhang & Nikurashin, 2020) and thus can potentially contribute to the ACC transport sensitivity to winds. The eddy dissipation processes occur at spatial scales that are much smaller than the horizontal resolution of eddy‐resolving ocean models (Fox‐Kemper et al., 2019) and are currently not accurately represented in models.…”
Section: Introductionmentioning
confidence: 99%